What is the right blood hematocrit preparation procedure for standards and quality control samples for dried blood spot analysis?. (February 2015) - Koster, Remco A; Alffenaar, Jan-Willem C; Botma, Rixt; Greijdanus, Ben; Touw, Daan J; Uges, Donald RA; Kosterink, Jos GW
Remco Koster is a research analyst and PhD candidate at the University Medical Center Groningen and University of Groningen. He has been working in the field of bioanalysis for over 13 years, where he has developed numerous analytical methods using LC–MS/MS. His main research focus is the influence of various matrices on the development and performance of analytical methods using LC–MS/MS. The development of high-speed extraction and analysis methods for drugs and drugs of abuse in human matrices like blood, plasma, hair, saliva and dried blood spots often leads to improved procedures for preparation of standards and quality control samples, sample handling and validation. Two hematocrit preparation procedures for standards and quality control samples were evaluated in order to improve the quality of procedures for dried blood spot validation and analysis.